2023
DOI: 10.3390/su15043433
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Social Structures in Cowpea Varietal Demands for Women and Men Farmers in Segou Region, Mali

Abstract: Cowpea is the second most consumed leguminous crop after groundnut in Mali. Its national production was 260,000 tons in 2018. It contributes to nitrogen fixation in the soil. The improved varieties of cowpea cultivars contain traits such as high grain yield, drought resistance, and early maturity. However, the adoption of improved cowpea varieties remains low. The non-participation and or non-consideration of the needs of men and women farmers in the varietal selection process contributed to the low adoption r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These studies (Rabé et al, 2022;10.3389/fsoc.2023.1260407 Frontiers in Sociology 09 frontiersin.org Karikari et al, 2023;Moussa et al, 2023), however, assumed preference for traits among producers and end-users to be genderblind, therefore did not consider trait preferences for both men and women. From the study, the finding that more women preferred pods that grow above the canopy for the reason that such cowpea are easier to harvest confirms (Ridgeway, 2009;Sylla et al, 2023) that gender relations fit into social structures that define agricultural tasks. Such tasks such as harvesting of cowpea as generally done by women may also define trait choices by women farmers.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These studies (Rabé et al, 2022;10.3389/fsoc.2023.1260407 Frontiers in Sociology 09 frontiersin.org Karikari et al, 2023;Moussa et al, 2023), however, assumed preference for traits among producers and end-users to be genderblind, therefore did not consider trait preferences for both men and women. From the study, the finding that more women preferred pods that grow above the canopy for the reason that such cowpea are easier to harvest confirms (Ridgeway, 2009;Sylla et al, 2023) that gender relations fit into social structures that define agricultural tasks. Such tasks such as harvesting of cowpea as generally done by women may also define trait choices by women farmers.…”
Section: Discussionmentioning
confidence: 58%
“…The observation from the sex-disaggregated focus group discussions that women had limited access to land can be considered as one of the social barriers to adoption in northern Ghana. The nexus between gender relations and social structures also define access to land and other agricultural inputs (Ridgeway, 2009;Sylla et al, 2023). Rules embedded in communities regulate activities, decision and roles mostly in favour of men to the disadvantage of women (Kabeer, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The implication is that majority of cowpea farmers in the study area are married. Married farmers are expected to be more committed to cowpea production enterprise as source of income due to family responsibilities attached to the status (Sylla et al, 2023). Regarding household size of the respondents, 48.3 percent indicated 5 persons or less, while the average household size of all respondents was 6±3.94 persons.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that access to input markets (e.g., certified seeds) is likely influenced by various factors, including household wealth (livestock and land), access to finance and extension services (knowledge), distance to the nearest input market, and input source [5,9,10]. Efforts such as Cowpea Innovation Platforms (CIPs) that include financial institutions have helped smallholder farmers access loans and expand their crop production [8,20,35]. The adoption of seeds of improved varieties by smallholder farmers is not solely a matter of agronomic choice but is deeply entwined with socio-economic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sociocultural norms and gender inequalities can influence farmers' access to certified seeds due to limited control over resources, restricted decision-making power, and unequal access to extension services and credit [17][18][19]. For instance, a study conducted in Mali showed that men are more likely than women to participate in trials, innovation platforms, field visits, and demonstration plot activities, making them quick adopters of newly released cowpea varieties [20].…”
Section: Introductionmentioning
confidence: 99%